An approach to solve motorail transportation loading layout optimization problem: the China case - Huang, Wencheng; Shuai, Bin (Transport, 2022)
In this paper, we formulate a cost and safety oriented approach to optimize the motorail transport car loading layout optimization problem. The model has 2 objective functions, one maximizes the wagon loading weight utilization rate, and another minimizes the gravitational center height after loading the cars on the wagons. The calculation results show that: the heaviest cars should be loaded in the middle of the decks, the cars weight loaded on both sides should be gradually reduced; the total weight of cars loaded on lower deck should be larger than the total weight of cars loaded on the upper deck.